1998
DOI: 10.1177/0739456x9801700404
|View full text |Cite
|
Sign up to set email alerts
|

Goal Achievement, Relationship Building, and Incrementalism: The Challenges of University-Community Partnerships

Abstract: The University of Illinois at Chicago's Neighborhoods Initiative is used as a case study of how planning occurs in a situation of shared power; what the relationship is between the goals of participants and what actually gets done; and what the role of planners is in linking knowledge to action. The collaborative planning model is characterized by incrementalism, and relationship building is a key element. Relationship building and goal achievement are not opposites; the achievement of goals requires some leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 4 publications
0
31
1
Order By: Relevance
“…To be sure, faculty, staff and residents had similar perceptions regarding the influence of the town-gown relationship on employment and job training, educational benefits, and graduation rates. These findings did not correspond to those of Gilderbloom and Mullins (1995); Wiewel and Lieber (1998); and the U. S. Department Housing and Urban Development (2003). The results from the research conducted by the above researchers revealed that the town-gown relationship between HBCUs and their communities did provide a significant impact on the sustainability of employment and job training, educational benefits, and graduation rates within these communities.…”
Section: Discussioncontrasting
confidence: 69%
“…To be sure, faculty, staff and residents had similar perceptions regarding the influence of the town-gown relationship on employment and job training, educational benefits, and graduation rates. These findings did not correspond to those of Gilderbloom and Mullins (1995); Wiewel and Lieber (1998); and the U. S. Department Housing and Urban Development (2003). The results from the research conducted by the above researchers revealed that the town-gown relationship between HBCUs and their communities did provide a significant impact on the sustainability of employment and job training, educational benefits, and graduation rates within these communities.…”
Section: Discussioncontrasting
confidence: 69%
“…The characteristics and outcomes of partnerships depend on a number of factors, including prior relationships and motivations (Maurrasse 2001;Wiewel and Lieber 1998), the leadership abilities of partners (Peters et al 2006;Weiss et al 2002), competing institutional demands (Bringle et al 1999;El-Ansari and Phillips 2004;Groark and McCall 1996;Israel et al 1998;Maurrasse 2001;Ward 2003), and trust and the balance of power (Israel et al 1998;Peters et al 2006).…”
Section: Characteristics Of Effective Partnershipsmentioning
confidence: 97%
“…Their expert knowledge of the communities in which they work are the key ingredient to building bottom-up solutions to health issues. However, due to several challenges in building partnerships with academic institutions, a topic that goes beyond the scope of this discussion, these collaborations are often difficult to initiate and maintain (Wiewel and Lieber, 1998;Wolff and Maurana, 2001;Suarez-Balcazer et al, 2005). By facilitating this process with students early on in their academic or professional careers, it is possible to instill first-hand knowledge of the benefit of these collaborations in our work, and in doing so build future capacity for students to address 'real-world' issues in our communities and populations (Seifer and Vaughn, 2004).…”
Section: Discussionmentioning
confidence: 99%